SOSIALISASI DAN PELATIHAN TEKNOLOGI BUDIDAYA IKAN NILA SISTEM BIOFLOK PADA KELOMPOK USAHA BERSAMA - Waode Munaeni; Muhammad Aris; Ismi Musdalifah Darsan; Rusmawati Labenua; Disnawati Disnawati (Jurnal Abdi Insani, 2022)
Intensive cultivation of tilapia at high densities causes high waste, which can result in low water quality. This will also make it easier for fish to get sick. Another problem in tilapia cultivation is the high use of feed. These problems cause low productivity in tilapia aquaculture. One solution is to cultivate tilapia using the biofloc system. The biofloc system has been shown to increase fish growth, improve water quality, and the floc that forms can be used as a feed source, reducing the need for artificial feed. The purpose of this community service activity is to provide insight regarding tilapia farming using biofloc technology and training on how to make biofloc for tilapia cultivators in fish farming groups in Lake Ngade. Activities are carried out at Fitu Village, near Lake Ngade, from June to August 2022. Activities include: 1) socialization with the aim of broadening tilapia cultivators' insights using biofloc technology; 2) hands-on training on how to make floc in buckets, flock measurement, stocking tilapia, rearing, and harvesting. The results of the socialization activities were able to pique the participants' interest and increase their knowledge, particularly those of the tilapia cultivators in Lake Ngade, about the biofloc material provided. It can be seen from the interaction between participants and resource persons regarding the material provided during socialization activities. During the training activities, cultivators follow all stages, starting from how to make flocks, measuring flocks, stocking tilapia, rearing them, and harvesting them. During rearing, the practices given are 1) feed management; 2) flock volume measurement and flock management; and 3) measurement of several water quality parameters such as pH, temperature, hardness, nitrite, and nitrate. The conclusion from this community service activity is that the socialization and training carried out can increase the participants' insights and skills, especially for tilapia cultivators using biofloc technology, starting from the method of making flocks, measuring flocks, stocking tilapia, maintenance, including feeding and measuring quality water, and harvest.